Relevansi Sistem Keuangan Publik Islam Terhadap Pengelolaan dan Pembelanjaan Di Indonesia Telaah Kitab Al-Kharaj Karya Abu Yusuf - Dwi, Trisna; Ayu, Diyan Putri (Institut Agama Islam Sunan Giri Ponorogo, 2024)
In terms of people’s welfare, the government is obliged to provide, maintain and operate public utilities to ensure the fulfillment of social interests. This thesis reports the results of research with a problem formulation, (1) How is the Islamic public finance system in Abu Yusuf’s Al-Kharaj Book? (2) What is the relevance of Islamic public finance from Abu Yusuf’s perspective on management and expenditure policies in Indonesia? This research uses a qualitative approach with the type of literature research. The data collected in this research was taken from literature (library research). To get the best possible data, the author refers to the book written by Abu Yusuf with the title Al-Kharaj and also researches a number of literature, namely collecting data by reading books, journals and other forms of data to complement the data. After the author examines and examines Abu Yusuf’s thoughts on Islamic Public Financial Management written in the Book of Al-Kharaj, namely (1) The results of the discussion show that the Book of Al-Kharaj not only discusses the tax system but also discusses in detail the state revenue system from kharaj , ‘ushr, ghanimah and fai’, jizyah, zakat, and public ownership. (2) The results of this research show that the relevance of state income and state expenditure.